Editorial: The Hobbesian Revolution - Castel de Lucas, Gustavo; Fernández Peychaux, Diego A. (Las Torres de Lucca. International Journal of Political Philosophy, 2016)
We suggest a reading of Hobbes’s works as a revolution, as a radical break with the dominant tradition. A break that affects almost all realms, but specially those of political, moral and judicial thought. Moreover, we try to suggest that this revolutionary thought remains alive and useful for today’s politics.